A cold and power cogeneration system utilizing LNG cryogenic energy and low-temperature waste heat. (February 2019) - Li, Yongyi; Zhang, Guoqiang; Liu, Yujia; Song, Xiaowei; Yang, Yongping
Abstract: A novel cold and power cogeneration system is proposed in this paper. In the system, a "special" absorption refrigeration cycle is designed which is driven by liquefied natural gas (LNG) cryogenic energy with ammonia-water as working fluid. And this system contains two power processes, in which ammonia and natural gas are heated respectively by low-temperature heat source and then expanse in turbines. The thermodynamic performance of the cogeneration system is simulated and analyzed. The results show that the new cogeneration system demonstrations good thermal performance. The exergy efficiency of the system is as high as 36.1%. The coefficient of performance (COP) of the refrigeration cycle is 1.6 and the generating efficiency of power cycle reaches 38.8%. Sensitive analyses are performed to evaluate the effects of key parameters on the performance of the cogeneration system. Some values of the key parameters are recommended and the variations of the main thermodynamic characters are outlined. This new cogeneration system provides a new approach for the efficient utilization of LNG cold energy.